2003
DOI: 10.7326/0003-4819-138-4-200302180-00008
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Therapy after Tumor Ablation Improves Prognosis in Patients with Hepatocellular Carcinoma Associated with Hepatitis C Virus

Abstract: After tumor ablation by ethanol injection, interferon therapy may enhance patient survival in selected patients with chronic hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
249
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(262 citation statements)
references
References 38 publications
11
249
1
1
Order By: Relevance
“…Other RCTs, also performed in Japan and Taiwan, failed to find a significant delay in the first recurrence with IFN therapy, but the second or third recurrence was significantly reduced especially in sustained responders and the overall survival was improved [401,402]. Another RCT in Italy did not detect effects of IFN therapy on early recurrence but late recurrence, with more than 2 years of interval, seemed to be reduced among IFN responders [403].…”
Section: Tertiary Prevention Of Hcv-related Hccmentioning
confidence: 94%
“…Other RCTs, also performed in Japan and Taiwan, failed to find a significant delay in the first recurrence with IFN therapy, but the second or third recurrence was significantly reduced especially in sustained responders and the overall survival was improved [401,402]. Another RCT in Italy did not detect effects of IFN therapy on early recurrence but late recurrence, with more than 2 years of interval, seemed to be reduced among IFN responders [403].…”
Section: Tertiary Prevention Of Hcv-related Hccmentioning
confidence: 94%
“…Since the first RCT of IFN adjuvant therapy appeared in 2000 [45], four other RCTs have been published [46][47][48][49]. Studies have indicated that IFN decreases the rate of HCC recurrence, and the results of our meta-analysis, totalling 196 patients, consistently show a statistically significant benefit on HCC recurrence.…”
Section: Interferonmentioning
confidence: 55%
“…Therefore, all these data underscore, from a practical point of view, the need for adjuvant therapy (tertiary prevention) in the effort to prolong survival and reduce recurrence rates. In the past, different anticancer agents have been evaluated for tertiary prevention of HCC recurrence, including retinoids [42], intra-arterial I-131 [43], adoptive immunotherapy [44], and finally IFN [45][46][47][48][49]. Recently, sorafenib, an oral multi-kinase inhibitor targeting both tumor cells and the tumor vasculature is being evaluated in the setting of tertiary chemoprevention.…”
Section: Tertiary Chemopreventionmentioning
confidence: 99%
“…Promising results have been reported by adaptive immunotherapy (Takayama et al, 2000) and selective radiotherapy (Lau et al, 1999), which ideally would act on unrecognized disseminated tumor nests. Similarly, retinoid administration (Muto et al, 1996) and interferon therapy (Shiratori et al, 2003) have also been suggested to be active in preventing metachronic HCC. Unfortunately, none of the available data suffice to incorporate any of these options in conventional clinical practice (Bruix and Sherman, 2005).…”
Section: Surgical Resectionmentioning
confidence: 99%